2012
DOI: 10.2174/092986612800793208
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptides from Marine Organisms: A Short Overview

Abstract: Marine organisms are an immense source of new biologically active compounds. These compounds are unique because the aqueous environment requires a high demand of specific and potent bioactive molecules. Diverse peptides with a wide range of biological activities have been discovered, including antimicrobial, antitumoral, and antiviral activities and toxins amongst others. These proteins have been isolated from different phyla such as Porifera, Cnidaria, Nemertina, Crustacea, Mollusca, Echinodermata and Craniat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 85 publications
0
30
0
1
Order By: Relevance
“…The previously described lead optimization work was strongly focused on KOR affinity and peptide stability optimization. To ensure that while improving activity, selectivity for KOR was not lost, we investigated selected key milestone molecules (1,6,23,26,39,44,48), where strong structural changes were made, for their receptor selectivity. The selectivity profile of dynA (1− 17) and selected peptides, e.g., 1, 6, 23, 26, 39, 44, 48 at other opiate receptors (Table 3) indicated that improvements in KOR affinity paralleled improvements in KOR selectivity relative to MOR, DOR, and NOP.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…The previously described lead optimization work was strongly focused on KOR affinity and peptide stability optimization. To ensure that while improving activity, selectivity for KOR was not lost, we investigated selected key milestone molecules (1,6,23,26,39,44,48), where strong structural changes were made, for their receptor selectivity. The selectivity profile of dynA (1− 17) and selected peptides, e.g., 1, 6, 23, 26, 39, 44, 48 at other opiate receptors (Table 3) indicated that improvements in KOR affinity paralleled improvements in KOR selectivity relative to MOR, DOR, and NOP.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Seaweeds are abundant and produce bioactive molecules derived from their primary (lipids, proteins, and carbohydrates) and secondary metabolism (alkaloids, terpenes, poliketides steroids) with a variety of pharmacological and ecological functions (Teixeira 2010), as antiviral, antibacterial, antifungal, antitumoral, anticoagulant, andothers (El-Gamal 2010). In addition, these molecules have a great diversity on their chemical structure compared with terrestrial organisms (Suleria et al 2015;Lazcano-Pérez et al 2012). This wide range of properties makes living marine organisms a promising source of molecules to develop drugs to treat diseases or pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, marine organisms offer a unique genetic pool that may possess the potential of treating several diseases including rare diseases or the ailments that are still considered incurable (Demunshi and Chugh, 2010;Lazcano-Pérez et al, 2012). This can be effectively deduced from the successfully FDA approved drugs (Table 1) such as Cytarabine (Ara-C), vidarabine (Ara-A), ziconotide, trabectedin, eribulin mesylate (Mayer et al, 2010;Martins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The communities have been deprived of fair and equitable sharing of the benefits arising from the commercialization of their knowledge. According to Global Industry Analysts, marine bioresources were expected to give rise to 'marine biotechnology' products worth over $3.75 bn by 2012, particularly functional ingredients for nutritionals, cosmetics and pharmaceuticals (Meredith, 2010) and while according to another market report by TechNavio, the marine biotech market is anticipated to grow at a CAGR of 3.82% over the period 2012-2016(Global Marine Biotech Market, 2012-2016.…”
Section: Introductionmentioning
confidence: 99%